Metabolic Consequences of Neuronal HIF1α-Deficiency in Mediobasal Hypothalamus in Mice - Rozjan, Azmat; Shan, Weibi; Yao, Qiaoling (Frontiers in Endocrinology, 2021)
Objective This study aims to investigate whether hypoxia-inducible factor 1α (HIF1α) in the neurons of the mediobasal hypothalamus is involved in the regulation of body weight, glucose, and lipid metabolism in mice and to explore the underlying molecular mechanisms. Methods HIF1αflox/flox mice were used. The adeno-associated virus that contained either cre, GFP and syn, or GFP and syn (controls) was injected into the mediobasal hypothalamus to selectively knock out HIF1α in the neurons of the mediobasal hypothalamus. The body weight and food intake were weighed daily. The levels of blood glucose, insulin, total cholesterol (TC), triglyceride (TG), free fatty acid (FFA), high-density lipoprotein (HDL), and low-density lipoprotein (LDL)were tested. Intraperitoneal glucose tolerance test (IPGTT) was performed. The insulin-stimulated Akt phosphorylation in the liver, epididymal fat, and skeletal muscle were examined. Also, the mRNA expression levels of HIF1α, proopiomelanocortin (POMC), neuropeptide Y (NPY), and glucose transporter protein 4 (Glut4) in the hypothalamus were checked. Results After selectively knocking out HIF1α in the neurons of the mediobasal hypothalamus (HIF1αKOMBH), the body weights and food intake of mice increased significantly compared with the control mice (p < 0.001 at 4 weeks). Compared with that of the control group, the insulin level of HIF1αKOMBH mice was 3.5 times higher (p < 0.01). The results of the IPGTT showed that the blood glucose level of the HIF1αKOMBH group at 20–120 min was significantly higher than that of the control group (p < 0.05). The serum TC, FFA, HDL, and LDL content of the HIF1αKOMBH group was significantly higher than those of the control group (p < 0.05). Western blot results showed that compared with those in the control group, insulin-induced AKT phosphorylation levels in liver, epididymal fat, and skeletal muscle in the HIF1αKOMBH group were not as significantly elevated as in the control group. Reverse transcription-polymerase chain reaction (RT-PCR) results in the whole hypothalamus showed a significant decrease in Glut4 mRNA expression. And the mRNA expression levels of HIF1α, POMC, and NPY of the HIF1αKOMBH group decreased significantly in ventral hypothalamus. Conclusions The hypothalamic neuronal HIF1α plays an important role in the regulation of body weight balance in mice under normoxic condition. In the absence of hypothalamic neuronal HIF1α, the mice gained weight with increased appetite, accompanied with abnormal glucose and lipid metabolism. POMC and Glut4 may be responsible for this effect of HIF1α.